1994
DOI: 10.1002/ana.410350507
|View full text |Cite
|
Sign up to set email alerts
|

Decreased concentrations of GLUT1 and GLUT3 glucose transporters in the brains of patients with Alzheimer's disease

Abstract: Glucose metabolism is depressed in the temporal and parietal regions of the cortex in patients with Alzheimer's disease. We measured the concentrations of two glucose transporters, GLUT1 and GLUT3, in six regions of brains from both control subjects and patients with Alzheimer's disease. The concentrations of both transporters were reduced in the cerebral cortex, with larger and highly significant reductions observed for GLUT3, the putative neuronal glucose transporter. The reductions in GLUT3 were greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
245
0
2

Year Published

1997
1997
2019
2019

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 442 publications
(273 citation statements)
references
References 39 publications
26
245
0
2
Order By: Relevance
“…Initial studies by Kalaria and Harik (59) demonstrated a reduction in the 55-kDa form of GLUT1 in cerebral microvessels prepared from Alzheimer's patients compared with normal age-matched controls (60). These observations were confirmed and extended in studies by Simpson et al, who also demonstrated a loss of the 45-kDa glial form of GLUT1 and a striking loss of GLUT3 protein expression in parietal, occipital, and temporal cortex, together with caudate nucleus and hippocampus; only the frontal cortex did not show any significant loss (109). Importantly, the decreases in GLUT3 in the parietal and temporal cortices, hippocampus, and caudate were still significant even after correction for overall neuronal loss using the synaptic protein SNAP25 as a marker.…”
Section: Neuronal Glut3 and Cerebral Glucose Utilizationsupporting
confidence: 77%
“…Initial studies by Kalaria and Harik (59) demonstrated a reduction in the 55-kDa form of GLUT1 in cerebral microvessels prepared from Alzheimer's patients compared with normal age-matched controls (60). These observations were confirmed and extended in studies by Simpson et al, who also demonstrated a loss of the 45-kDa glial form of GLUT1 and a striking loss of GLUT3 protein expression in parietal, occipital, and temporal cortex, together with caudate nucleus and hippocampus; only the frontal cortex did not show any significant loss (109). Importantly, the decreases in GLUT3 in the parietal and temporal cortices, hippocampus, and caudate were still significant even after correction for overall neuronal loss using the synaptic protein SNAP25 as a marker.…”
Section: Neuronal Glut3 and Cerebral Glucose Utilizationsupporting
confidence: 77%
“…Glucose is primarily delivered from the extracellular space into neurons via the insulin‐independent glucose transporter GLUT3, and the insulin‐dependent GLUT4,46, 47 though many other GLUTs contribute. AD is characterized by downregulation of neuronal GLUT3 and glial/endothelial GLUT1, which provides far fewer avenues for glucose uptake into either cell type and thus leads to a reduction in neuronal activity and metabolism 48, 49. Large projection neurons are particularly vulnerable to these metabolic disruptions in AD due to their exceptionally high‐energy requirements coupled with their reliance on GLUT3 for glucose uptake 50, 51.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, rarefaction of cortical capillary beds has recently been reported in Alzheimer's disease (17). Second, Glut-1 expression is decreased in postmortem brain tissue from demented individuals (18)(19)(20). These structural and biochemical abnormalities are likely to contribute to impaired blood flow and the integrity of the physical blood brain barrier, impeding the brain's supply of oxygen, energy, and nutrients, and the removal of toxins from the brain (21).…”
Section: Discussionmentioning
confidence: 99%